Implementasi dan Implikasi Awig-awig dalam Konsep Tri Hita Karana pada Kehidupan Masyarakat Adat Bali - G.A Kristha Adelia Indraningsih (Belom Bahadat, 2020)
Awig-awig is a legal product of a traditional organization in Bali, which is made deliberately by consensus by all members. These rules serve as guidelines for the behavior of the members of the organization concerned. Every traditional village has awig-awig which is based on the Tri Hita Karana philosophy (three basic principles of happiness). Parahyangan, namely customary rules that govern the lives of members of the community in establishing a harmonious relationship with the God, Pawongan, namely customary rules regarding relationships between humans in certain customary villages, Palemahan, namely Awig-awig which regulates how the relationship between members of the traditional village and nature the surroundings. The application of awig-awig encounters several obstacles, namely the lack of understanding of the people regarding awig-awig, the lack of firmness in giving sanctions, the lack of a sense of togetherness. Awig-awig implications for the implementation of Tri Hita Karana to strengthen the application of Tri Hita Karana which is very influential on human life. If the agreed awig-awig is implemented properly, then the Tri Hita Karana concept indirectly has been implemented properly so that Hindu harmony can be established in the traditional village.